Over half MAC sevoflurane in cesarean section - Siriwan Jirasiritham (2018)
Half MAC(minimal alveolar concentration) of volatile anesthetics has been commonly used with nitrous oxide for cesarean section which could occur intraoperative awareness. Over half MAC or more than 1% sevoflurane was studied on 65 parturients who came for either elective or emergency operations. The patient characteristics were age 31.00 ± 5.67 (21-41) years, BW 72.37 ± 10.51 (52.6-117) kg, and ASA physical status 1, 52% for elective and 73% for emergency cases. The indications for operations were mostly CPD, fetal distress and previous cesarean sections. The anesthetic time was 59.19 ± 17.35 (35-145) minutes while the induction-delivery time was 12.72 ± 5.66 (3-28) minutes. General anesthesia was rapid sequence induction with prepofol or thiopental and tracheal intubation under succinylcholine with the application of cricoid pressure. The depth of anesthesia was maintained with 1.5-3% sevoflurane until delivery and the volatile agent was lowered to 0.4-1%, adjusted to clinical manifestation. Midazolam and morphine were added postdelivery. Data of hemodynamic changes during delivery, neonatal outcome and intraoperative blood loss were analyzed without any remarkable note. The postoperative interview on recalls confirmed adequate depth of anesthesia. It was concluded that sevoflurane at more than 1% concentration could be used predelivery in cesarean sections on the issues of awareness, hemodynamics and fetal conditions but caution was suggested in terms of uterine relation effect which was dose-dependent.